2012
DOI: 10.5897/jmpr12.406
|View full text |Cite
|
Sign up to set email alerts
|

Alkaloids and flavonoids from the air dried aerial parts of Citrullus colocynthis

Abstract: From the air dried aerial parts of Citrullus colocynthis, two new alkaloids namely, 2-(nonan-8-one)-(1H)-4-quinolone and 2-(Nonan-8-one) 4-methoxy-quinoline were isolated. Two flavonoids, (2S)-3 \ , 4 \methylenedioxy-5, 7-dimethoxy flavan and hispidulin 7-(6-E-β coumaroyl-β-D glucopyranoside) were also extracted and identified. The structures were established by conventional methods of analysis and confirmed by UV, IR, 1 H and 13 CNMR, and mass spectra.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…The leaf area and leaf area index are major indicators for determining the solar radiation interception, canopy photosynthesis which ultimately results growth and development rate of the crop. The results are in accordance with the findings of Hadiat and Salman (19) who reported that the shoot length, root length, leaf area, chlorophyll, carbohydrate and protein contents of the maize were increased significantly with increase in the concentration of silver nanoparticles from 20 to 60 ppm over control.…”
Section: A) Particle Size Analysissupporting
confidence: 92%
“…The leaf area and leaf area index are major indicators for determining the solar radiation interception, canopy photosynthesis which ultimately results growth and development rate of the crop. The results are in accordance with the findings of Hadiat and Salman (19) who reported that the shoot length, root length, leaf area, chlorophyll, carbohydrate and protein contents of the maize were increased significantly with increase in the concentration of silver nanoparticles from 20 to 60 ppm over control.…”
Section: A) Particle Size Analysissupporting
confidence: 92%
“…These compounds were more abundant and varied in the fruit parts of the latter species. The emission of fluorescence under UV light that characterizes many fluorescing phytochemicals, such as aromatic alkaloids and tetracyclic isoprenoids having conjugated ring systems in which electron movement, or de-localization, between bonds is possible, supports the proposal that the major fluorescent bands mentioned above could correspond to yet to be defined lipophilic alkaloids similar to the quinolone alkaloids detected in Citrullus colocynthis, a medicinal Cucurbitaceae annual plant [63]. Another possibility is that they could represent one or more compounds resembling foetidissimoside A, a 3,28-bidesmosidic triterpenoid saponin previously reported in C. foetidissima roots [64,65].…”
Section: Discussionmentioning
confidence: 54%
“…He showed that alcohol extract of colocynth leaves is more effective than alcohol extracts of roots and fruits, which is explained by the higher content of flavonoids and phenolic compounds in the leaves of C. colocynthis. -2012. -Vol.…”
Section: Fig 4 Sod Activity In Liver Homogenate In Rats Of Experimementioning
confidence: 99%